Germination and seedling growth of Echinochloa frumentacea L. under various levels of NaCl stress - M. Santhoshkumar, K. Parkash, T. Ravimycin, (Journal of Plant Stress Physiology)
An investigation was conducted to assess the effect of NaCl on vegetative growth of Barnyard Millet (Echinochloa frumentacea) were germinated in petri-dishes lined with blotting paper. The seeds were treated with 25, 50, 75 and 100 mM NaCl, with distilled water as control. The germination percentage and the growth parameters were observed. The obtained result showed that the germination rate germination percentage, root length, shoot length of the (Echinochloa frumentacea) were gradually decreased with increased concentrations of NaCl stress. The highest inhibitions of germination and morphological parameters observed in 50 mM NaCl concentration treated seedlings. The highest germination and growth parameters recorded in control of seedlings. Result showed that the lowest concentrations of treatments were increased in all the analyzed parameters. Moreover, increasing concentration the negative effect of results was obtained. Further study to be studied with effect of NaCl on biochemical and enzymatic activities of Barnyard millet.